Carbon Footprint Estimation in Road Construction: A Case Study of Pokhara-Mugling Road, Nepal - Khanal, Sabhyata; Dongol, Robert (Everest Advances in Science and Technology, 2025)
Road construction is a significant contributor to greenhouse gas emissions within the transport sector. This study attempted to quantify the Green House Gases (GHGs) emission of Pokhara - Mugling Road using Life Cycle Assessment (LCA). A Gate-to-Gate LCA was conducted to quantify emissions. Sensitivity analyses were conducted to assess the differential impacts of bitumen and aggregate on emissions during construction. The Relative Importance Index (RII) was calculated by distributing a questionnaire to experts and environmental safeguard specialists to gather insights on the most suitable mitigation measures for reducing emissions in Nepal’s road sector. The findings revealed that the total carbon equivalent emissions from the construction of the Pokhara - Mugling Road amounted to 33.73 kilotons of CO2e. Notably, 60.78% of these emissions were attributed to the materials used in the construction process. Fuel consumption by the Hot Mix Asphalt (HMA) plant contributed 70% of the emissions from the total fuel consumption, surpassing the emissions from all other plants and equipment involved in the pavement construction. Sensitivity analysis results indicated that changes in bitumen content have a more significant effect on GHG emissions compared to variations in aggregate. This suggests that the construction of a national highway substantially contributes to carbon emissions, and therefore, requires careful consideration to minimize its environmental footprint. Based on the RII analysis, optimizing construction and quality management plans is essential for reducing greenhouse gas emissions in road construction. Equally important is using electricity as a fuel source for heating in asphalt production can lower emissions compared to traditional fossil fuels. Implementing warm mix or cold asphalt technologies and incorporating recycled materials such as Reclaimed Asphalt Pavement (RAP) and crumb rubber in asphalt mixtures can significantly reduce emissions. Transitioning to low-emission equipment, including electric or biodiesel-powered machinery, and adopting alternative energy sources such as natural gas or biomass-based fuels in asphalt plants also can minimize the environmental impact. By integrating these sustainable practices, road construction in Nepal can significantly decrease its contribution to greenhouse gas emissions.